Small island nations can achieve food security benefits through climate-adaptive blue food governance by 2050. (May 2023) - Teneva, Lida; Free, Christopher M.; Hume, Andrew; Agostini, Vera N.; Klein, Carissa J.; Watson, Reg A.; Gaines, Steven D.
Abstract: Small island nations are highly dependent on food from aquatic environments, or blue food, and vulnerable to climate change and global food market price volatility. By 2050, rising populations will demand more food through various protein sources, including from the sea. This study identifies which small island nations can improve food self-sufficiency from the sea by implementing tailored climate-adaptive fisheries governance strategies that adapt to shifting marine resources. We combined projections of seafood demand and local catch under different future scenarios of global carbon emissions and local adaptive fisheries management to estimate potential seafood surpluses or deficits from by 2050 for 31 small island nations worldwide. We find that adapting fisheries management every 10 years could mitigate even worst-case projections of climate change impacts on locally available seafood, building a seafood surplus by 2050 in the Seychelles, Maldives, Cabo Verde, Bahamas, Antigua and Barbuda, Kiribati, PNG, Fiji, FSM, Tuvalu, and Marshall Islands. Strategic financial and capacity investments by the international community could help realize the full potential of food security from the sea for those nations. However, we project deficits in locally caught seafood by 2050 in Comoros, Sao Tome and Principe, Mauritius, Barbados, Dominican Republic, Cuba, Dominica, Jamaica, Grenada, St. Lucia, St. Vincent and the Grenadines, Trinidad and Tobago, Haiti, Palau, Samoa, Nauru, and the Solomon Islands, regardless of adapting fisheries management. For those nations, we recommend international collaboration that strengthens food security from sources other than the sea coupled with investments in locally sustainable aquaculture. Overall, we find that climate-adaptive fisheries management can benefit a range of the studied small island nations, by supporting both food security goals as well as economic goals of productive fisheries for international trade